Muhammadiyah as the Socio-Political Foundation of Masyumi in Selayar 1950–1960 - Rahmatul Yushar (JURNAL JAWI, 2026)
This article discusses the relationship between Masyumi and Muhammadiyah in Selayar using historical research methods (Heuristic, Verification, Interpretation, and Historiography). The historical sources used are archival sources related to Masyumi. The research results show that Masyumi became the party with the third-largest number of members in South Sulawesi and the largest in Selayar. The main factor that caused Masyumi to be well-received in Selayar was the Masyumi party officials who also served as members of Muhammadiyah. The role of several Muhammadiyah figures who also held positions in the Masyumi Party in Selayar includes; K.H. Haiyyung, the founder of Muhammadiyah who became the Chairman of the Masyumi Council of Scholars, Ma’galatung Dg. Pasolong, the Chairman of the Selayar Branch of Muhammadiyah on July 30, 1940, who became the chairman of the Selayar Branch of Masyumi at its inception, Sulaeman Abbas, a young Muhammadiyah figure who became the Chairman of the Selayar Branch of the Masyumi Party in its early period, Rauf Rahman, a Muhammadiyah figure who became the Chairman of the Masyumi Party replacing Sulaeman Abbas around the end of 1952, and Abdul Kadir Kasim, the Chairman of the Selayar Branch of Muhammadiyah from 1951-1968 who became the Chairman of the Masyumi Party around 1958 until Masyumi was dissolved. From this research, it is proven that the alignment of Muhammadiyah and Masyumi did not only occur in national-level politics but also in local-level politics. In the end, this research contributes to the strengthening of national identity in the millennial era.